The Impact Of Corporate Social Responsibility Perception On Brand Credibility, Brand Reputation And Purchase Intention (Case Studi: Student Mechanic Competition At Vacational High School In The Greater Jakarta Area) - Fathoni Syarief, Achmad Achsin; Durman, Theodosia Yunita; Hanoum, Syarifa (Jurnal Ekonomi, 2024)
Corporate Social Responsibility (CSR) is a concept that has become a primary focus for companies in their efforts to build a positive image and fulfill their social responsibilities. Although various studies have demonstrated the significant impact of CSR on brand equity, brand credibility, and consumer purchase intention, research involving educational institutions in the context of CSR remains relatively limited. This study aims to analyze the CSR program of a distribution company for MRO (Maintenance, Repair, Overhaul) equipment and its impact on brand equity, brand credibility, and purchase intention. The CSR program focuses on a mechanical competition for students at Vocational High Schools (SMK) in the Greater Jakarta area (Jabodetabek). This research adopts an explanatory quantitative approach to test theories or hypotheses in order to support or refute previous findings. Data were collected through the distribution of questionnaires to all vocational education mentors involved in the mechanical competition at SMKs in the Jabodetabek region. The sample was determined using the Hair formula, resulting in 150 respondents. The collected data were then analyzed using SEM-PLS software. The research findings show that the proposed model highlights the significant role of Corporate Social Responsibility (CSR) as a key factor influencing various dimensions of brand management. CSR not only contributes to enhancing brand credibility and brand reputation but also has a significant impact on strengthening brand equity, which in turn plays a role in increasing consumer purchase intention. The results of this study provide a foundation for companies and vocational schools to develop CSR strategies that can improve brand equity, brand credibility, brand reputation, and purchase intention.